MANAJEMEN KEGIATAN BELAJAR MENGAJAR BERBASIS DIGITAL DI SDN SAMBIROTO: Penelitian Kualitatif - Harum K., Sri Maya; Kholiq Permoino, Gilar; Rokhmat; Sulianto, Joko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digitalization of teaching and learning management (KBM) has become a crucial strategy for enhancing the effectiveness and flexibility of education, particularly in elementary schools. This study explores the implementation of KBM digitalization at SDN Sambiroto, Kecamatan Kunduran, Kabupaten Blora, focusing on strategies, challenges, and the impact of technology on learning quality. Using a qualitative approach with a case study method, this research examines the use of various digital platforms, such as Google Classroom, Quizizz, Canva, and Powtoon, to support the learning process. The findings indicate that KBM digitalization has improved student engagement and the efficiency of lesson delivery, aligning with the study by Gunawan et al. (2024) on the benefits of Learning Management Systems (LMS) in elementary education. However, key challenges remain, including teacher readiness, digital access inequality among students, and technological infrastructure limitations, as highlighted in studies by Santoso & Widodo (2024) and UNESCO Digital Learning Week (2025).To overcome these obstacles, SDN Sambiroto has implemented several strategies, such as teacher digital literacy training, hybrid learning development, and collaborations with educational and technology institutions to enhance digital accessibility for students. This study underscores that successful KBM digitalization heavily depends on educational policy support, teacher preparedness, and adequate technological infrastructure.The findings provide recommendations for educational institutions seeking to develop more effective, inclusive, and sustainable digital learning systems, ultimately contributing to the improvement of elementary education in Indonesia.